Combined Depth and Subdural Electrodes for Lateralization of the Ictal Onset Zone in Mesial Temporal Lobe Epilepsy with Hippocampal Sclerosis - Junhyung Kim; Joong Koo Kang; Sang Ahm Lee; Seok Ho Hong (Brain Sciences, 2023)
(1) Objective: This study aimed to explore the efficacy of conventional invasive techniques in confirming unilateral seizure onset localization in mesial temporal lobe epilepsy with hippocampal sclerosis (MTLE-HS) and to investigate the association between electrode type and intracranial electroencephalography (EEG) pattern. (2) Methods: This retrospective study encompasses patients diagnosed with MTLE-HS who underwent an invasive study prior to an anterior temporal lobectomy (ATL). Intracranial EEG features were assessed for 99 seizure events from 25 selected patients who achieved seizure remission with ATL after an invasive study using bilateral combined depth and subdural electrodes. Their findings were compared to those of 21 seizure events in eight patients who exhibited suboptimal seizure outcomes. (3) Results: For the distribution of electrodes that recorded the ictal onset, hippocampal depth electrodes recorded 96% of all seizure events, while subdural electrodes recorded 52%. Among the seizures recorded in subdural electrodes, 49% were localized in medial electrodes, with only 8% occurring in lateral electrodes. The initiation of seizures exclusively detected in hippocampal depth electrodes was associated with successful seizure remission, whereas those solely recorded in the lateral strip electrodes were often linked to refractory seizures after ATL. (4) Conclusions: These findings emphasize the importance of employing a combination of depth and subdural electrodes in invasive studies for patients with MTLE-HS to enhance the accuracy of lateralization. This also cautions against sole reliance on subdural electrodes without depth electrodes, which could lead to inaccurate localization.